HISTORIA E IDEOLOGÍA BAJO HUGO CHÁVEZ - Medeiros Arce, Anatólio (2012)
This article argues that Venezuela's internal political context remains heavily shaped by ideologies once thought obsolete by the late 20th century. Unlike other nations, Venezuela’s political dynamic revolves around ideological debates, particularly socialism and the glorification of historical figures like Simón Bolívar. History plays a key role in the state apparatus, especially when connecting present realities to symbolic figures or their descendants, such as Hugo Chávez and his great-grandfather. The Venezuelan government promotes a specific interpretation of Western, American, and national history, using it as a powerful tool to legitimize and maintain the Chávez regime. This challenges Francis Fukuyama's thesis of the "End of History" and the "Death of Ideologies," which emerged after the fall of the Soviet Union but failed to capture many ongoing realities. Venezuela stands out as an exception; during the 1960s and 1970s, it was seen as a democratic model in a region filled with authoritarian regimes. Today, however, the persistence and even growth of socialist ideologies in the country show that economic crises have not led to the disappearance of ideological influence. On the contrary, these ideals continue to gain electoral strength, particularly as neoliberalism faces a deep legitimacy crisis across Latin America.